Pendampingan Home Industry Dalam Menghadapi Era 5.0 Di Desa Arisan Gading Kabupaten Ogan Ilir - Muhammad Febrianza; Trecy Austin; Diany Putri Pratiwi (CV. Multi Kreasi Media, 2023)
Implementation of community service activities in Arisan Gading Village, South Indralaya District, Ogan Ilir Regency, in the form of developing a home industry so that it is better known to many people in South Sumatra and at the national level. The problem in Arisan Gading Village is the lack of use of social media or the lack of training received by the community regarding small and medium enterprises. Facing the 5.0 era, a human-centered and technology-based society. The community is expected to be able to solve various social challenges and problems by using various innovations that emerged in the Industrial Revolution 4.0 era to improve people's quality of life. The purpose of this activity is to help home industry entrepreneurs starting from how to manufacture products, product packaging, and product sales. The method used is outreach, training and mentoring, and evaluation for 31 days in 2022. As a result of this activity the local community can be more confident and product sales are increasing with the expansion of the market with online media.